Assessment of post-traumatic stress disorder and well-being among Sudanese during the ongoing war: a cross-sectional study - Mohamed Fakhry Hussein; Marina Saleeb; Basma Tolba; Yasmine Yousry Mohamed; Assem Gebreal; Abuelgasim Osman Alemam Mohamed; Faisal Saeed Al-Qahtani; Fatima Mohamed Osman Yasin; Omelhassan Abdelgader Alawed; Ramy Mohamed Ghazy (BMC Psychology)
Abstract Background Wars profoundly impact mental health with growing long lasting consequences. This study assessed the prevalence of post-traumatic stress disorder (PTSD) and well-being among Sudanese affected by the ongoing conflict, with a specific focus on healthcare workers (HCWs). Methods A cross-sectional study was conducted between April 1 and June 30, 2024, using the validated Arabic versions of PTSD Checklist for the Diagnostic and Statistical Manual of Mental Disorders (DSM-5) (PCL-5) and the World Health Organization (WHO)-5 Well-Being Index. Results A total of 1022 participants were included, and 44% were recruitted through online questionnaire and face-to-face interviews. Their mean age was 31.4 ± 12.5 years, 63.4% were females, 16.3% were HCWs and 83.3% were displaced due to conflict. The mean score of PTSD was 35 ± 21.3 with 56.9% having PTSD. The mean well-being score was 55.0 ± 23.9 with 40% reporting poor well-being. Among HCWs, 60.5% suffered from PTSD and 27.5% experienced poor well-being. A significant negative correlation was observed between PTSD and well-being scores (r=-0.273, p < 0.001). Predictors of PTSD were being male [β = -10.91, 95% confidence interval (CI) (-13.44, -8.38); p < 0.001], urban area resident [β = -10.38, 95%CI (-18.78, -1.98); p = 0.016], non-medical profession [β = 5.07, 95%CI (1.46, 8.67); p = 0.006], living with 2 to 10 households [β = 6.69, 95%CI (0.46, 12.91); p = 0.035], living with more than 20 households [β = 13.20, 95%CI (4.17, 22.23); p = 0.004], insufficient income [β = 4.32, 95% CI (1.84,6.81); p = 0.001], living in conflict zones [β = 13.38 95%CI (8.83,17.92); p < 0.001], refugee resettlement [β = 13.18, 95%CI (9.98,16.38); p < 0.001], and well-being score [β = -0.20, 95%CI (-0.25, -0.15); p < 0.001]. Predictors of well-being scores were living with more than 20 households [β = -17.44, 95%CI (-28.83, -6.04); p = 0.003], being a HCW [β =-6.22, 95%CI (-11.87, -0.57); p = 0.031], being a student [β = -7.55, 95%CI (-12.94, -2.16), p = 0.006, insufficient income [β = -5.04, 95%CI (-8.17, -1.90); p = 0.002], and living in conflict zones [β = -8.22, 95%CI (-13.96, -2.48); p = 0.005]. Conclusions The study highlights an alarmingly high prevalence of PTSD among Sudanese including HCWs, with significant mental health consequences. These findings emphasize the urgent need for mental health interventions and humanitarian support to mitigate the psychological challenges faced by the conflict affected population.